Layanan Konseling Individu Melalui Pendekatan Rational Emotive Behavior Therapy Dalam Penangan Siswa Tidak Disiplin - Khobariah, Ainun; Tajiri, Hajir; Eryanti, Devi (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
Early childhood is a phase of rapid growth of the body and brain in optimizing its function. The objectives of this study are: To find out the habituation technique of Islamic character guidance for children through hijaiyah letter games; To find out the process of building children's Islamic character through hijaiyah letter games; To find out the results of Islamic character guidance for children through hijaiyah letter games. The results showed that, Islamic character guidance to improve children's character was successful, children understood the importance of religious, independent and cooperative characters. The method used is descriptive qualitative, namely the author intends to reveal the guidance process by collecting observation and interview data.